Litter C and N losses at different decomposition stages of Robinia pseudoacacia: The weaker effects of soil enzyme activities compared with those of litter quality and the soil environment - Su, Zhuoxia; Zhu, Xiaoyue; Wang, Yaobin; Mao, Shenglin; Shangguan, Zhouping (Frontiers in Environmental Science, 2022)
Litter decomposition promotes soil carbon and nitrogen cycling and is driven by litter quality, the soil environment and enzyme activities. The relative importance of these factors may change during the litter decomposition, however, very few studies have emphasized the temporal dynamics of these factors across plantation ecosystem, which limits our understanding of litter decomposition. To evaluate the temporal dynamic of above-mentioned litter decomposition drivers, we collected leaf and fine root litters from four different years of restoration of Robinia pseudoacacia on the Loess plateau of China and placed them on soil from the corresponding sites to incubate for 210 days. We constructed successive litter decomposition stages according to litter mass-loss interval, and we also used partial least squares path modelling (PLSPM) to evaluate the relative importance of these drivers. Our results showed that the C and N losses in leaf litter were significantly higher than those in root litter regardless of stand age. Leaf litter C and N losses increased with restoration duration, while root litter C and N showed an opposing trend with restoration duration, with the lowest levels of losses occurring at older stand ages. The initial litter quality, litter quality and the soil environment regulated leaf and root litter C loss, and enzyme activity also determined root C loss. Litter quality, the soil environment and enzyme activity influence leaf litter N loss, while root N loss was controlled by initial litter quality and the soil environment. Overall, enzyme activities had a relatively weak influence on litter C and N losses, and they impacted litter C and N losses only during the early stages. Therefore, our results revealed substantial differences in different restoration durations and litter types at the different decomposition stages, which has important significance for understanding carbon and nitrogen cycling on the Loess Plateau of China.